Development of Islamic Financial Literacy Media for I-Generation (Internet Generation) as an Effort to Build a Sharia Economic Society - Saiful Anwar (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2021)
This study aims to design the Islamic financial literacy media, implement the Islamic financial literacy media and evaluate the effectiveness of Islamic financial literacy media for i-generation. The research methods and techniques used are Research and Development (R&D), action research, and experimental research. Research and Development Research is used to develop and validate Islamic financial literacy products. Action Research and Experimental Research are used to observe the effectiveness of the implementation of financial literacy learning models. The object of this service is the madrasa aliyah students in Surakarta Karisidenan. The results of the need assessment found that the Islamic financial literacy media that is right for i-generation is an interactive Android-based e-book. This media can increase sharia financial literacy because the internet and android are very familiar and user friendly for i-generation. This research contribution in addition to providing interactive e-books is to form a Sharia Financial Smart Generation community for i-generation. This community can be used as a means of grounding Islamic finance from an early age to realize Indonesia as the center of the world Islamic economy. Other findings from the study found that i-generation was also interested in videograms or memes as a medium for obtaining information so that the media needed to be considered also as media literacy in the digital age.